Iteration Method for Evaluation of the Price of a Government Contract for Designing Defense Aviation Equipment - V. P. PANAGUSHIN; V. YU. IVANISOV; V. I. LAPENKOV; N. K. CHAIKA (Стратегические решения и риск-менеджмент, 2017)
An approach to finding reasonable prices developmental works on creation of aviation equipment for defense purposes is based on the method of successive approximations.The content of this method, its advantages and the reasons limiting its use is disclosed. Practical steps for its implementation in enterprises-performers of ROC of aviation technology for defense purposes are proposed.